The Influence Of Social Media Marketing Activities On Brand Loyalty Through Cognitive Engagement, Emotional Engagement, Brand Trust And Brand Equity - Yunishafira, Affiya; Sugiat, Maria Apsari; Hidayah , Riski Taufik (International Journal Labs, 2025)
This study aims to examine the influence of social media marketing (SMM) consisting of entertainment, interaction, trendiness, customization, and electronic word of mouth (eWOM) on brand loyalty for GT Man underwear products. Additionally, it explores the mediating roles of cognitive engagement, emotional engagement, brand trust, and brand equity in enhancing the relationship between SMM and brand loyalty. A quantitative approach was employed using structural equation modeling-partial least squares (SEM-PLS) through SmartPLS 4.0. Data were collected from 400 social media users familiar with GT Man to test both direct and indirect effects among the proposed constructs. The findings indicate that all dimensions of SMM significantly affect the mediating variables and brand loyalty. The strongest direct effect is found between SMM and brand trust, suggesting that consistent, authentic, and responsive social media communication builds greater trust in GT Man. In terms of mediation, cognitive engagement and brand trust serve as the most influential mediators in the formation of brand loyalty. While emotional engagement and brand equity have relatively weaker indirect effects, they still play a significant role in strengthening the impact of SMM. This research contributes to the theoretical understanding of how psychological engagement and brand perceptions shape loyalty in a digital environment. Practically, it suggests that GT Man should develop more educational, emotionally resonant, and interactive social media content to reinforce trust, perceived value, and long-term customer loyalty.